1997
DOI: 10.1136/adc.77.6.516
|View full text |Cite
|
Sign up to set email alerts
|

Clinicians' abilities to estimate cardiac index in ventilated children and infants

Abstract: Objectives-To evaluate the ability of clinicians involved in the provision of paediatric intensive care to estimate cardiac index in ventilated children, based on physical examination and clinical and bedside laboratory data. Methods-Clinicians were exposed to all available haemodynamic and laboratory data for each patient, allowed to make a physical examination, and asked to first categorise cardiac index as high, high to normal, low to normal, or low, and then to quantify this further with a numerical estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
118
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(124 citation statements)
references
References 17 publications
1
118
0
5
Order By: Relevance
“…In critically ill neonates, cardiac output is usually estimated from the interpretation of several clinical variables, such as blood pressure, urine output, blood gas analysis, and capillary refill. Tibby and colleagues (4) showed that clinicians using these indirect parameters of cardiac performance were unable to predict the actual cardiac output in ventilated children and infants. The same was shown in ventilated adults (5).…”
mentioning
confidence: 99%
“…In critically ill neonates, cardiac output is usually estimated from the interpretation of several clinical variables, such as blood pressure, urine output, blood gas analysis, and capillary refill. Tibby and colleagues (4) showed that clinicians using these indirect parameters of cardiac performance were unable to predict the actual cardiac output in ventilated children and infants. The same was shown in ventilated adults (5).…”
mentioning
confidence: 99%
“…Furthermore, clinical assessment of cardiac output in children is notoriously unreliable [17]. Even invasive monitoring may be unhelpful.…”
Section: Whither?mentioning
confidence: 99%
“…No obstante, es conocido que la habilidad del clínico para juzgar los parámetros hemodinámicos es pobre 31 .…”
Section: "Tiempo Es Tejido"unclassified